Oceanography and Marine Biology, an Annual Review, Volume 41 2003
DOI: 10.1201/9780203180570-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Minimum Zone Benthos: Adaptation and Community Response to Hypoxia

Abstract: Mid-water oxygen minima (Ͻ0.5 ml l Ϫ1 dissolved O 2 ) intercept the continental margins along much of the eastern Pacific Ocean, off west Africa and in the Arabian Sea and Bay of Bengal, creating extensive stretches of sea floor exposed to permanent, severe oxygen depletion. These seafloor oxygen minimum zones (OMZs) typically occur at bathyal depths between 200 m and 1000 m, and are major sites of carbon burial along the continental margins. Despite extreme oxygen depletion, protozoan and metazoan assemblages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 184 publications
(347 reference statements)
0
18
0
2
Order By: Relevance
“…The experimental chamber effect was included to address pseudo-replication. For these models, fixed-and randomeffect terms were tested using the function anova and ranova (R package lmerTest; Kuznetsova et al, 2017), respectively, whilst post hoc pairwise comparisons were computed on estimated marginal means using emmeans (R package emmeans; Lenth, 2021). The ratio of expanded papillae in P. crocea from experiment 2 and expansion ratio in S. australiensis from experiment 3 were investigated using repeated-measure univariate PERMANOVA (Anderson, 2001(Anderson, , 2014 because it did not meet the normality assumption for mixed-effects models.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental chamber effect was included to address pseudo-replication. For these models, fixed-and randomeffect terms were tested using the function anova and ranova (R package lmerTest; Kuznetsova et al, 2017), respectively, whilst post hoc pairwise comparisons were computed on estimated marginal means using emmeans (R package emmeans; Lenth, 2021). The ratio of expanded papillae in P. crocea from experiment 2 and expansion ratio in S. australiensis from experiment 3 were investigated using repeated-measure univariate PERMANOVA (Anderson, 2001(Anderson, , 2014 because it did not meet the normality assumption for mixed-effects models.…”
Section: Discussionmentioning
confidence: 99%
“…The observed shifts in the relative occurrence frequency from the bottom to surface waters during hypoxia can be a result of upward movements of individuals or higher mortality in the bottom (Diaz & Rosenberg, 2008; Levin, 2003). As fish are highly mobile, they can respond sharply to the environmental changes by avoiding unfavorable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the reduced concentration of DO in the bottom water to a critical level imposes extreme stress for demersal organisms, such as increased mortality rates (Hrycik et al, 2017; Levin, 2003). Therefore, the species‐sorting paradigm (Figure 1a) expects that species that do not possess morphological or physiological traits adapted to the hypoxic conditions are likely to be filtered out from the bottom water (Bickler & Buck, 2007; Kodama & Horiguchi, 2011; Levin, 2003), and different species composition between bottom and surface water is expected during that season. In contrast, it is also probable that the bottom hypoxia was so intense that many species suffer from it or actively avoid it to a similar extent (Eby & Crowder, 2002; Pihl et al, 1991), and species can be apparently neutral with respect to the responses to the severe hypoxia, weakening the effect of species sorting (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that the Northeast Pacific OMZ had expanded at a rate of 3.0 ± 0.7 m/year in the last 60 years and had lost 15% of its oxygen (Ross et al, 2020). Low oxygen levels could increase the dominance of benthos tolerant to anoxic conditions (Levin, 2003). For example, one foraminifer genus Earlandia flourished as the major "disaster form" in the MU after the first PTME pulse (Figure 9A) and probably migrated from the Chibi site during the Early Triassic transgression.…”
Section: Marine Euxinia/anoxiamentioning
confidence: 99%
“…6.2 log mm 3 in the end-Permian, which fell to 5.5 log mm 3 after the mass extinction (Song et al, 2011). The reduction in size and diversity of fauna with calcified skeletons have been linked to oxygen shortage in modern oceans (Byers, 1978;Levin, 2003). Laboratory experiments showed that the oxygen consumption rate increased significantly in foraminiferal specimens larger than 250 mm (Bradshaw, 1961).…”
Section: Marine Euxinia/anoxiamentioning
confidence: 99%